2021
DOI: 10.1007/s11274-021-03163-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations detected from drug resistant Mycobacterium tuberculosis isolated from North East of Thailand

Abstract: The emergence of drug-resistant tuberculosis is a major global public health threat. Thailand is one of the top 14 countries with high tuberculosis, tuberculosis co-infected with Human Immunodeficiency Virus (HIV) and multi-drug resistant tuberculosis rates. Immediate detection of drug-resistant tuberculosis is necessary to reduce mortality and morbidity by effectively providing treatment to ameliorate the formation of resistant strains. Limited data exist of mutation profiles in Northeastern Thailand. Here, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Since 2017, several new single nucleotide polymorphisms (SNP) for KatG which are associated with INH resistance have been isolated, and some are summarized herein (Table S1) (Figure 4A). Thwe et al (2021) performed a study using PCR and DNA sequencing in 65 drug-resistant Mtb isolates, revealed a number of new mutations on katG (Thwe et al, 2021). A novel single nucleotide polymorphism (SNP) that causes INH resistance was identified in two of the studied isolates.…”
Section: Resistance To Inhmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2017, several new single nucleotide polymorphisms (SNP) for KatG which are associated with INH resistance have been isolated, and some are summarized herein (Table S1) (Figure 4A). Thwe et al (2021) performed a study using PCR and DNA sequencing in 65 drug-resistant Mtb isolates, revealed a number of new mutations on katG (Thwe et al, 2021). A novel single nucleotide polymorphism (SNP) that causes INH resistance was identified in two of the studied isolates.…”
Section: Resistance To Inhmentioning
confidence: 99%
“…A novel single nucleotide polymorphism (SNP) that causes INH resistance was identified in two of the studied isolates. This mutation is the substitution of proline for arginine at position 365 (P365R) (Thwe et al, 2021). This mutation was not characterized, however, although the residue P365 is more than 16Å away from the KatG active site, it was assumed to cause INH resistance.…”
Section: Resistance To Inhmentioning
confidence: 99%
“…Research in Thailand has primarily focused on understanding drug resistance, including specific mutations in genes associated with resistance ( 7 ). Recent studies have identified novel mutations in drug-resistant TB strains across different regions of Thailand ( 8 ). Additionally, drug-resistant TB has been observed among Thai children ( 5 ).…”
Section: Introductionmentioning
confidence: 99%